Unsteady effect on the propulsive force in the arm pull of crawl swimming - Matsuuchi, K. (1st International Scientific Conference of Aquatic Space Activities, 2008)
Generation of propulsive force in swimming was investigated. In knowing the mechanism of the generation information on the complex hand motion and the unsteady flow are important. The conventional quasi-steady theory cannot give the correct understandings on the generating mechanism of the propulsive force. The role of unsteadiness is critical in the generation of momentum and therefore in the force production. Two high-speed cameras determined the hand trace including the time variation of the geometry of a palm. It was found that the reduced frequency for the variation is too high to neglect the unsteadiness and the hand speed of the elite swimmer is not necessarily fast, which cannot be explained by the quasi-steady theory.